Comparative Evaluation of Graphene Oxide, Zinc Oxide, and Zinc Sulfide Nanoparticles in Carbomer-HPMC for Enhanced Wound Healing - Moradian Haftcheshmeh, Yousef; Tabatabae, Tahereh Sadat; Tabatabai, Tayebeh Sadat; Salehi, Majid; Shirshahi, Vahid (Shahroud Journal of Medical Sciences, 2025)
Background: Wounds are treated using various approaches, including hydrogel dressings and nanoparticles (NPs). Hydrogel dressings provide a cooling effect that promotes wound healing, while NPs such as graphene oxide (GO), zinc oxide (ZnO), and zinc sulfide (ZnS) enhance cellular activity and accelerate the healing process. This study aimed to investigate the effects of GO, ZnS, and ZnO NPs loaded with carbomer 980 and HPMC polymers on wound healing.Methods: The mechanical and physical properties of the scaffolds were evaluated using FTIR, SEM, pH monitoring, degradation rate, water absorption, blood clotting index (BCI), and hemolysis tests. Biocompatibility and cell migration were assessed via MTT assay, DAPI staining, and scratch tests. In addition, full-thickness (15 mm × 15 mm) wounds were created in animal models, and wound healing was evaluated using Verhoeff-Van Gieson and hematoxylin-eosin staining.Results: GO-based hydrogels exhibited superior biocompatibility, wettability, controlled degradation, enhanced cell viability, and accelerated cell migration compared to ZnS- and ZnO-based formulations when combined with carbomer 980 and HPMC polymers. Histological analysis revealed increased collagen and elastin synthesis, enhanced angiogenesis, and greater epidermal thickness.Conclusions: The prepared hydrogels show promising potential for wound healing applications. Further clinical studies are warranted to validate their therapeutic efficacy.